The Agro Exports of Organic Native Products and Environmental Security in Peru - Coayla, Edelina; Bedón, Ysabel (European Journal of Economics and Business Studies, 2020)
The study objective is to analyze agro-exports of organic products and environmental security (certification) in Peru. Agro-exports are the second generator of foreign currency for Peru. The descriptive, comparative-graphical method and the polynomial curve are used. In 2019 traditional agro-exports and non-traditional agro-exports contributed 11% and 89% of total agro-exports respectively, the main markets were the United States (35%) and the Netherlands (15%). Peru is the world's leading exporter of native functional products (called superfoods) quinoa and maca. Quinoa is the most demanded native agro-export product internationally. It was found that during the period 2000-2019 the main Peruvian agro-exports of non-traditional products with a vertiginous growth are fruits and vegetables. For the year 2019, fruit agro-exports in terms of FOB value in millions of US - contribute 56% to the total of non-traditional agro-exports. The increase in fresh grapes, fresh blueberries and fresh avocados is remarkable. Environmental security in terms of the area for organic production affects 51% of agro-exports. Peru promotes organic production from the producer to the final consumer and the certification of organic products in the production, transformation and marketing processes.